Advantages of automatic injector MEDRAD® Avanta with manual operation of contrast agent injection in interventional radiology - A. G. Osiev; N. L. Shimanovskii (Вестник рентгенологии и радиологии)
Advantages of automatic injector MEDRAD® Avanta in interventional radiology are described. The issues concerning the selection of the optimal contrast agent during angiography and endovascular interventions are considered. It is concluded that contrast enhancement with iopromide and automatic injector MEDRAD® Avanta should be considered as reliable, highly effective and safe imaging technique in the diagnosis and X-ray surgery in cardiovascular diseases, malformations, tumors and other patology